How does voice matter? Evidence from the ultimatum game - Riyanto, Yohanes Eko (2013)
Prior research has demonstrated that the ability to express one’s views or “voice” matters in social and economic interactions, but little is known of the mechanisms through which voice operates. Using an experimental approach based on the ultimatum game with the strategy method, we explore four potential channels for voice that encompass and expand on prior work: the knowledge effect of voice, the value expressive (or inherent value) of voice, the expectation effect of voice, and the procedural fairness effects of voice. Our results show strong effects through the value expressive and expectation channel, but not through either the knowledge channel or procedural fairness. In our view, voice is powerful because people like to express their views and they are disappointed when their views did not make a difference in their outcomes.